Decentralizing governance: exploring the dynamics and challenges of digital commons and DAOs - Esposito, Mark; Tse, Terence; Goh, Danny (Frontiers in Blockchain, 2025)
This paper explores the intersection of decentralized governance, blockchain technology, and the digital commons through the lens of Elinor Ostrom’s principles. It examines how Decentralized Autonomous Organizations (DAOs) and tokenization models present both opportunities and risks for managing digital resources in transparent, community‐driven ways. The authors assess how token‐based, reputation‐based, and hybrid governance mechanisms—ranging from quadratic voting to Soulbound Tokens—can enhance democratic participation and accountability within blockchain ecosystems, while also recognizing their susceptibility to plutocracy, voter apathy, and collusion. Drawing on case studies such as MakerDAO, MolochDAO, Commons Stack, and Aragon, the paper critically analyzes real‐world implementations of decentralized governance and the extent to which they adhere to—or deviate from—Ostrom’s design principles for common‐pool resource management. It highlights structural limitations in governance design, especially in the presence of unequal voting power and centralized control disguised as decentralization. The paper also critiques the socio-economic implications of blockchain’s global expansion, noting how digital governance can replicate neo-colonial dynamics in the Global South and amplify state surveillance in authoritarian contexts. Further, it underscores the environmental costs of blockchain infrastructure and introduces DAOs like KlimaDAO and Regen Network as emerging experiments to align decentralized finance with sustainability goals. Ultimately, the authors propose a “dual imperative”: to develop context‐sensitive, inclusive governance architectures within DAOs, while pursuing international legal recognition and standards. The conclusion calls for communitarian models that fuse algorithmic rule enforcement with human-centered deliberation to protect the emancipatory potential of blockchain governance. Whether blockchain becomes a force for democratization or digital enclosure, the authors argue, will depend on how its governing architectures are designed, contested, and evolved by the communities that steward them.